PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL STORYTELLING BERBASIS NEARPOD MENGGUNAKAN METODE PAIRED STORYTELLING DI KELAS IV SEKOLAH DASAR - Alfiana, Rinta; Maryono; Muhammadin Al Fath, Ayatullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Nearpod-based digital storytelling learning media using the paired storytelling method in Indonesian language learning for fourth-grade elementary school students. The background of this study is based on the low narrative writing skills of students caused by the use of conventional and less interactive learning media. This study employed a Research and Development method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were teachers and fourth-grade students at SDN 68/VI Empang Benao. Data were collected through observation, interviews, questionnaires, and expert validation sheets. The results showed that the Nearpod-based digital storytelling learning media using the paired storytelling method was categorized as highly valid by experts, practical based on teachers’ and students’ responses, and effective in increasing students’ engagement and understanding of narrative text material. The implementation results indicate that students became more active, motivated, and able to write narrative texts with more coherent structures, therefore the developed media is suitable to be used as an innovative alternative learning media in Indonesian language learning at the elementary school level.